Metamorphism and thrust tectonics in the Munsiari Group of Central Crystalline Zone of Garhwal Himalaya, India - Singh, S. P.; Singh, V. K.; Saklani, P. S. (Journal of Nepal Geological Society, 1998)
The Munsiari Group of the Central Crystalline Zone of Garhwal Himalaya comprises low to medium grade metamorphics of pelitic and psarnmitic rocks along with granitoids and gneisses. The textural and structural studies indicate that these rocks witnessed two strong tectonothermal metamorphic episodes (M1 and M2) The allochthonous rocks of the M1 metamorphic episode are highly deformed and had undergone Tertiary intracontinental shortening and superposed metamorphism. The crystallisation, possibly initiated during the D1 deformation phase, continued upto the D2 deformation and biotite-chlorite (Bio-Chi), gamet-chlorite (Gt-Chi) and kyanite-staurolite (Ky-St) zones were developed. The porphyritic granitoids were emplaced at the end phase of the M1 metamorphism. The M2 phase of metamorphism occurred discordant to the M1 episode and was mainly confined to the shears and are syntectonic to the movement of the Main Central Thrust. The P-T conditions inferred that metamorphism for M1 episode took place at 400-600 °C/ 4-6 Kbar and at 300-500 °Cl 4-5 Kbar for the episode.